2018
DOI: 10.1073/pnas.1807751115
|View full text |Cite
|
Sign up to set email alerts
|

ERβ-mediated induction of cystatins results in suppression of TGFβ signaling and inhibition of triple-negative breast cancer metastasis

Abstract: Triple-negative breast cancer (TNBC) accounts for a disproportionately high number of deaths due to a lack of targeted therapies and an increased likelihood of distant recurrence. Estrogen receptor beta (ERβ), a well-characterized tumor suppressor, is expressed in 30% of TNBCs, and its expression is associated with improved patient outcomes. We demonstrate that therapeutic activation of ERβ elicits potent anticancer effects in TNBC through the induction of a family of secreted proteins known as the cystatins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 46 publications
(48 reference statements)
5
44
0
1
Order By: Relevance
“…Future studies should also be performed to determine if cell-type specific signaling through ERα in the liver and/or hypothalamus underlies the metabolic and lifespan-extending effects of 17α-E2. ChIP-Sequencing and RNA-Sequencing: U2OS-ERα cells were harvested 24 hours post-treatment and chromatin immunoprecipitation was performed as previously described [106,107]. Briefly, ERα was immunoprecipitated overnight at 4ºC using 10 µg of Flag antibody (clone M2, Sigma-Aldrich, St. Louis, MO).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also be performed to determine if cell-type specific signaling through ERα in the liver and/or hypothalamus underlies the metabolic and lifespan-extending effects of 17α-E2. ChIP-Sequencing and RNA-Sequencing: U2OS-ERα cells were harvested 24 hours post-treatment and chromatin immunoprecipitation was performed as previously described [106,107]. Briefly, ERα was immunoprecipitated overnight at 4ºC using 10 µg of Flag antibody (clone M2, Sigma-Aldrich, St. Louis, MO).…”
Section: Discussionmentioning
confidence: 99%
“…ERβ elicites tumor-suppressive effects, particularly with regard to suppression of metastatic phenotypes, which is characterized by the induction of a family of secreted proteins known as cystatins and the subsequent inhibition of canonical transforming growth factor (TGF-β) signaling [89], leading to decreased expression of a network of genes related to extracellular matrix, cell invasion and vitamin D3 metabolism [90]. There is evidence that ERβ is involved in angiogenesis in breast cancer.…”
Section: Roles Of Erβ In Breast Cancer Cell Migration and Invasionmentioning
confidence: 99%
“…The attenuation of AP-1 and Sp1 mediated estradiol induced transcriptional activation is a potential, although not clearly established, mechanism for inhibition (132) and the AF1 domain of ERβ is necessary for this effect (133,134). In regard to TNBC, Reese et al suggested that ERβ induced the up-regulation of secreted proteins known as cystatins that down-regulate canonical TGFβ signaling, is critical for the suppression of the metastatic phenotype (135).…”
Section: Erβ Expression and Role In Various Cancer Typesmentioning
confidence: 99%